Effect of Simvastatin Administration on ALP (Alkaline Phosphatase) Level in Wistar Rat's Femur Fracture - Hery Susilo; Edi Mustamsir; Wanda Gusta Rai (Jurnal Kedokteran Brawijaya, 2022)
Metabolism of the bone healing process can be monitored by Bone formation marker, such as alkaline phosphate (ALP). Simvastatin is known to increase bone marker formation in the repair phase, but its effects on the ALP level have not been known yet. This study aimed to determine the effect of oral simvastatin administration on the expression of ALP level in femur fracture healing in a rat model of femur fracture. The research method was experimental post-test only using 18 Rattus norvegicus rats which were divided into 3 groups, namely the control group for femur fracture (Control), femoral fracture group and giving simvastatin 0.36 mg/day for 2 weeks (Treatment I), and femur fracture group and administration of simvastatin 0.36 mg/day for 4 weeks (Treatment II). ALP levels were measured at 0, 2, and 4 weeks. The results showed an increase in ALP levels in the simvastatin treatment group compared to the control group (p<0.05). It can be concluded that the administration of simvastatin increased ALP levels in rat femoral fractures.